Academic Self-efficacy, Academic Self-concept, and Impostor Phenomenon among High Achiever Students - Giriansyah, Syafira Putri; Qoyyimah, Nur Rohmah Hidayatul (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Academic achievements, which should ideally be a source of pride, can instead create pressure that has the potential to trigger impostor phenomenon in some students. This study aims to examine the role of academic self-efficacy and academic self-concept on impostor phenomenon among high achiever students in Malang City. A quantitative approach with a multiple regression design was employed in this study. The respondents consisted of 385 high achiever students, meeting the criteria of class year 2019-2021, aged 18-25 years, and having a GPA above 3.50. Several instruments were used in this study, including: 1) The Academic Self-efficacy Scale (TASES); 2) The Academic Self-concept Scale Short Form (ASCS-SF); and 3) The Clance Impostor Phenomenon Scale (CIPS). The results indicate that academic self-efficacy and academic self-concept have a significant effect on impostor phenomenon both partially and simultaneously, with a contribution of 24.1%. Prestasi akademik yang seharusnya menjadi suatu kebanggaan, justru dapat menimbulkan tekanan tersendiri yang berpotensi memicu impostor phenomenon bagi beberapa mahasiswa. Penelitian ini bertujuan untuk mengetahui peran academic self-efficacy dan academic self-concept terhadap impostor phenomenon pada high achiever student di Kota Malang. Penelitian ini menggunakan pendekatan kuantitatif dengan desain regresi berganda. Responden penelitian ini berjumlah 385 high achiever student dengan kriteria tahun angkatan 2019-2021, berusia 18-25 tahun, dan memiliki IPK diatas 3,50. Terdapat beberapa instrumen yang digunakan dalam penelitian ini, yaitu: 1) The Academic Self-efficacy Scale (TASES); 2) The Academic Self-concept Scale Short Form (ASCS-SF); dan 3) Clance Impostor Phenomenon Scale (CIPS). Hasil penelitian ini menunjukkan bahwa academic self-efficacy dan academic self-concept berpengaruh signifikan terhadap impostor phenomenon baik secara parsial maupun simultan, dengan sumbangan pengaruh sebesar 24,1%.